A base film for a composite current collector and a method for manufacturing the same
Patent Information
- Application Number
- CN202411522007.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-10-29
AI Technical Summary
[0004]但是对于以上复合集流体,由于所用高分子聚合物膜一方面表面极性较弱,其表面张力较低、表面粘附性能较弱,所制备的复合集流体中高分子聚合物基膜与金属层间的结合力较弱
[0028]本发明提供了一种复合集流体用基膜,其为聚合物极性材料层-聚合物强化材料层-聚合物极性材料层构成的夹心结构,能够最大程度兼顾边层和芯层性能,具有良好的耐温性、以及耐电解液性能。其中,在边层结构中加入极性材料,能够使边层具有较好的极性,有效提高表面张力,有利于后期与金属物质的复合;在边层结构中加入两性材料,能很好的将聚烯烃和极性材料融合在一起,使得材料整体上表现出均匀的极性;在边层结构中加入两性材料和聚烯烃,能很好的将边层和芯层粘结在一起,防止出现分层等不良现象。边层强极性物质以及两性物质的引入,能够有效的起到稳定结构的作用,从而防止器件的损坏。在芯层结构中加入强化物质,能加速聚烯烃的结晶,从而提高复合集流体用基膜的耐温性、强度和耐化学,从整体上提高了器件的安全性。
Smart Images

Figure BDA0005108261180000061 
Figure BDA0005108261180000071
Abstract
Description
Technical Field
[0001] This invention belongs to the field of current collector technology for lithium batteries, specifically a composite current collector base film and its preparation method. Background Technology
[0002] Due to the excellent conductivity of metallic materials, traditional current collectors are made of pure metal foil. Aluminum foil is used for the positive electrode and copper foil for the negative electrode, depending on the lithium battery's electrode potential. However, with technological advancements, traditional metal electrodes can no longer fully meet usage requirements. The main problem lies in balancing the contradiction between current collector thickness and mechanical strength. When the thickness decreases, the thickness of the active material coating on the current collector surface increases, increasing battery energy density, but also reducing mechanical strength, making the current collector more prone to deformation. Metal electrodes in current collectors can also produce large burrs, increasing the risk of battery short circuits or punctures, thus reducing battery safety.
[0003] With the further development of new energy battery technology, composite copper foil has attracted widespread attention from upstream and downstream industries. Currently, composite copper foil uses PET, PP, or PI as substrates. A 20-80 nm metal film layer is first prepared on the surface of a 4-6 micrometer thick film using magnetron sputtering. Then, electroplating is used to thicken the copper layer to 1-5 micrometers, resulting in an overall thickness of 5-8 micrometers for the composite copper foil, replacing traditional copper foil. Composite copper foil can save approximately 70% of copper, reducing material costs, while also solving problems such as reduced strength and burrs caused by thinning.
[0004] However, for the above-mentioned composite current collectors, the polymer film used has weak surface polarity, low surface tension, and weak surface adhesion, resulting in weak bonding between the polymer base film and the metal layer. Furthermore, the material's resistance to electrolytes is poor, leading to problems such as melt-through, metal layer detachment, and electrolyte contamination after prolonged use. This results in poor structural stability of the composite current collector, affecting its normal use.
[0005] Therefore, it is extremely important to develop a composite current collector with stable structure and good electrolyte resistance to improve the structural stability of current composite current collectors and promote the application of composite copper foil current collectors. Summary of the Invention
[0006] The purpose of this invention is to provide a base film for composite current collectors and its preparation method. The base film for composite current collectors has excellent resistance to electrolytes, strength, and temperature resistance, which can meet the development trend of current collectors.
[0007] The objective of this invention is achieved through the following technical solution:
[0008] A composite current collector base film includes two layers of polymer polar material and a polymer reinforcing material layer located between the two layers of polymer polar material; that is, the composite current collector base film is a sandwich structure composed of a polymer polar material layer, a polymer reinforcing material layer, and a polymer polar material layer.
[0009] The polymer polar material layer includes polyolefin, polar polymer, amphoteric material and antioxidant;
[0010] The polymer-reinforced material layer includes polyolefin, reinforcing material, and antioxidant.
[0011] In the above scheme, by adjusting the types of components in the edge layer (i.e., the polymer polar material layer), the edge layer achieves good surface adhesion, allowing it to bond well with metallic substances. By adjusting the types of components in the core layer (i.e., the polymer reinforcing material layer), the core layer exhibits better temperature resistance and strength than ordinary polypropylene films, thus increasing the overall strength of the base film and facilitating subsequent processing and applications. Compared to existing technologies, the composite current collector base film prepared by this invention significantly improves electrolyte resistance, strength, and temperature resistance, meeting the development trend of current collectors.
[0012] As some possible embodiments of this application, the polyolefins in the polymer polar material layer and the polymer reinforcing material layer are one or more of polypropylene, ethylene-acrylic acid copolymer, ethylene-acrylate copolymer, poly-1-butene, poly-4-methyl-1-pentene, and cyclic olefin polymers.
[0013] As some possible embodiments of this application, the polar polymer material is one or more of polyethylene terephthalate, polybutylene terephthalate, polyphenylene sulfide, polydiphenyl ether sulfone, polyvinylidene chloride, polycaprolactam, polydecylformamide, polyhexamethylene sebacate, polynonylurea, and poly[bis(trichloroethoxy)phosphazene]phosphazene.
[0014] As some possible embodiments of this application, the amphoteric material is one or more of the following: maleic anhydride-grafted PP, MAH-grafted PP, GMA-grafted PP, maleic anhydride-grafted PE, MAH-grafted PE, GMA-grafted PE, maleic anhydride-grafted POE, MAH-grafted POE, GMA-grafted POE, maleic anhydride-grafted EVA, MAH-grafted EVA, GMA-grafted EVA, maleic anhydride-grafted EPDM, MAH-grafted EPDM, GMA-grafted EPDM, maleic anhydride-grafted SEBS, MAH-grafted SEBS, GMA-grafted SEBS, methyl methacrylate-glycidyl methacrylate-ethyl propylene terpolymer, maleic anhydride-grafted acrylonitrile-butadiene-styrene terpolymer, styrene-maleic anhydride random copolymer, or styrene-maleic anhydride copolymer.
[0015] As some possible embodiments of this application, the reinforcing material is one or more of the following: carbon nanotubes, carbon fibers, silicon carbide whiskers, glass fibers, calcium silicate whiskers, wollastonite, brucite, pyrophyllite, talc, calcium carbonate, silicon dioxide, alum, titanium dioxide, calcium oxide, magnesium oxide, carbon black, mica, etc.; aliphatic carboxylic acid metal compounds, sorbitol benzylidene derivatives, aromatic carboxylic acid metal compounds, organophosphates and lignin and their derivatives, sodium benzoate, and bis(p-tert-butylbenzoic acid)carboxylated aluminum.
[0016] As some possible embodiments of this application, the antioxidants in the polymer polar material layer and the polymer reinforcing material layer are one or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(2,3-di-tert-butylphenyl) phosphite, and bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite.
[0017] As some possible embodiments of this application, the thickness of the base film for the composite current collector is 4-6 μm, and the thickness of the polymer reinforcing material layer is 50%-90% of the thickness of the base film for the composite current collector. Preferably, the thickness of the base film for the composite current collector is 4 μm-5 μm, and the thickness of the polymer reinforcing material layer is 60%-80% of the thickness of the base film for the composite current collector.
[0018] As some possible embodiments of this application, the polymer polar material layer comprises 50 to 95 parts by weight of polyolefin, 5 to 40 parts by weight of polar polymer material, 0.1 to 10 parts by weight of amphoteric material and 0.1 to 0.5 parts by weight of antioxidant.
[0019] As some possible embodiments of this application, the polymer reinforcing material layer comprises 89.5 to 99.8 parts by weight of polyolefin, 0.1 to 10 parts by weight of reinforcing material, and 0.1 to 0.5 parts by weight of antioxidant.
[0020] Therefore, to achieve the above objectives, the present invention also provides a method for preparing a base film for composite current collectors, comprising the following steps:
[0021] S1. Preparation of polymer polar materials: First, polyolefin, polar polymer material, amphoteric material and antioxidant are mixed evenly, then granulated by twin-screw extruder, and finally granulated by water cooling, air cooling and pelletizing to obtain polymer polar materials.
[0022] S2. Preparation of polymer-reinforced materials: First, the polyolefin, reinforcing material and antioxidant are mixed evenly, then granulated by a twin-screw extruder, and finally cooled by water, cooled by air and granulated to obtain the polymer-reinforced material;
[0023] S3. Preparation of composite current collector base film: First, cut polymer polar material and polymer reinforcing material into slices and dry them at 80-110℃ for 4-10h; then, feed the dried polymer polar material slices into a three-layer co-extrusion edge layer extruder and the polymer reinforcing material slices into a three-layer co-extrusion core layer extruder. After melt extrusion, the material is cooled by roller cooling at 40-110℃, and then subjected to longitudinal stretching, transverse stretching and shaping in sequence to obtain the composite current collector base film.
[0024] As some possible implementations of this application, in steps S1 and S2, the extrusion temperature of the twin-screw extruder is 150°C to 300°C; in step S3, the extruder temperature is 150°C to 300°C.
[0025] As some possible implementation methods of this application, the specific steps after the quenching roller cooling in step S3 are as follows:
[0026] After being preheated at 40–120°C, stretched longitudinally by 2–7 times at 120–160°C, and shaped at 130–180°C by a longitudinal stretching system, the material is sent to a transverse stretching system. After being preheated at 80–150°C, stretched transversely by 2–8 times at 140–190°C, and shaped at 140–200°C, a composite current collector base film with a thickness of 4 μm–6 μm is obtained.
[0027] Compared with the prior art, the beneficial effects of the present invention are:
[0028] This invention provides a composite current collector base film, which is a sandwich structure composed of a polymer polar material layer, a polymer reinforcing material layer, and another polymer polar material layer. This structure maximizes the performance of both the edge and core layers, exhibiting excellent temperature resistance and electrolyte resistance. The addition of polar materials to the edge layer structure imparts good polarity, effectively increasing surface tension and facilitating subsequent composite with metallic substances. The inclusion of amphoteric materials in the edge layer structure effectively fuses the polyolefin and polar materials together, resulting in uniform polarity throughout the material. Furthermore, the addition of both amphoteric materials and polyolefins to the edge layer structure effectively bonds the edge and core layers together, preventing delamination and other defects. The introduction of highly polar and amphoteric materials in the edge layers effectively stabilizes the structure, preventing device damage. The addition of reinforcing materials to the core layer structure accelerates the crystallization of polyolefins, thereby improving the temperature resistance, strength, and chemical resistance of the composite current collector base film, ultimately enhancing the overall safety of the device. Detailed Implementation
[0029] Part 1: Preparation of Polar Polymer Materials (Examples 1-4)
[0030] Example 1
[0031] All materials were pre-dried. 90 parts by weight of polypropylene, 8 parts by weight of polyethylene terephthalate, 1.8 parts by weight of maleic anhydride-grafted PP and 0.2 parts by weight of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] were mixed in a high-speed mixer at 300 rpm for 5 minutes. The mixture was then granulated in a twin-screw extruder at an extrusion temperature of 270±5℃ and an extruder speed of 120 rpm. After water cooling, air cooling and cutting into granules, the polymer polar material (1) was obtained.
[0032] Example 2
[0033] All materials were pre-dried. 70 parts by weight of polypropylene, 30 parts by weight of polycaprolactam, 8 parts by weight of GMA-grafted PP and 0.5 parts by weight of tris(2,3-di-tert-butylphenyl) phosphite were mixed in a high-speed mixer at 200 rpm for 5 minutes. The mixture was then granulated in a twin-screw extruder at an extrusion temperature of 240±5℃ and an extruder speed of 120 rpm. After water cooling, air cooling and cutting into granules, the polymer polar material (2) was obtained.
[0034] Example 3
[0035] All materials were pre-dried. 60 parts by weight of poly4-methyl-1-pentene, 29.6 parts by weight of polymethyl methacrylate, 10 parts by weight of GMA-grafted POE, 0.3 parts by weight of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 0.1 parts by weight of tris(2,3-di-tert-butylphenyl) phosphite were mixed in a high-speed mixer at 180 rpm for 4 minutes. Then, the mixture was granulated by a twin-screw extruder at an extruder temperature of 250±5℃ and an extruder speed of 130 rpm. After water cooling, air cooling and cutting into granules, the polymer polar material (3) was obtained.
[0036] Example 4
[0037] All materials were pre-dried. 70 parts by weight of polyethylene, 20 parts by weight of polyvinyl alcohol, 10 parts by weight of maleic anhydride-grafted POE, 0.3 parts by weight of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 0.1 parts by weight of tris(2,3-di-tert-butylphenyl) phosphite were mixed in a high-speed mixer at 180 rpm for 4 minutes. Then, the mixture was granulated by a twin-screw extruder at an extruder temperature of 160±5℃ and an extruder speed of 80 rpm. After water cooling, air cooling and cutting into granules, the polymer polar material (4) was obtained.
[0038] Part Two: Preparation of Polymer-Reinforced Materials (Examples 5-7)
[0039] Example 5
[0040] All materials were pre-dried. 98.8 parts by weight of polypropylene, 1 part by weight of silicon carbide whiskers, and 0.2 parts by weight of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] were mixed for 3 minutes at 200 rpm in a high-speed mixer. The mixture was then granulated by a twin-screw extruder at an extruder temperature of 200±5℃ and an extruder speed of 120 rpm. After water cooling, air cooling, and cutting into granules, polymer-reinforced material (5) was obtained.
[0041] Example 6
[0042] All materials were pre-dried. 97.9 parts by weight of polypropylene, 2 parts by weight of aliphatic carboxylic acid metal compound, and 0.1 parts by weight of tris(2,3-di-tert-butylphenyl) phosphite were mixed in a high-speed mixer at 200 rpm for 3 minutes. The mixture was then granulated in a twin-screw extruder at an extruder temperature of 220±5℃ and an extruder speed of 150 rpm. After water cooling, air cooling, and cutting into granules, polymer-reinforced material (6) was obtained.
[0043] Example 7
[0044] All materials were pre-dried. 99.2 parts by weight of polyethylene, 0.5 parts by weight of organophosphate, and 0.3 parts by weight of bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite were mixed in a high-speed mixer at 300 rpm for 5 minutes. The mixture was then granulated in a twin-screw extruder at an extruder temperature of 160±5℃ and an extruder speed of 145 rpm. After water cooling, air cooling, and cutting into granules, polymer-reinforced material (7) was obtained.
[0045] Part 3: Preparation of the base film for composite current collectors (Examples 8-11)
[0046] Example 8
[0047] The dried polymer polar material (1) was fed into a three-layer co-extrusion side layer extruder with a side layer extruder temperature of 250±5℃. The polymer reinforcing material (5) was fed into a three-layer co-extrusion core layer extruder with a core layer extruder temperature of 240±5℃. The extrusion thickness ratio of each side layer to the core layer material was 1:4. The material was melt-extruded, cooled by roller cooling at 80℃, and then preheated at 120℃, stretched longitudinally by 5 times at 140℃, and shaped at 150℃ in the longitudinal stretching system before being sent to the transverse stretching system. After preheating at 150℃, stretching transversely by 7 times at 170℃, and shaped at 175℃, a composite current collector base film with a thickness of 4μmm was obtained.
[0048] Example 9
[0049] The dried polymer polar material (2) was fed into a three-layer co-extrusion side layer extruder at a temperature of 240±5℃. The polymer reinforcing material (6) was fed into a three-layer co-extrusion core layer extruder at a temperature of 240±5℃. The ratio of side layer to core layer material was 1:2. The material was melt-extruded, cooled by rollers at 90℃, and then preheated at 120℃, stretched longitudinally by 6 times at 145℃, and shaped at 150℃ in a longitudinal stretching system. After being sent to a transverse stretching system, it was preheated at 150℃, stretched transversely by 7 times at 170℃, and shaped at 175℃ to obtain a composite current collector base film with a thickness of 4.5μmm.
[0050] Example 10
[0051] The dried polymer polar material (1) was fed into a three-layer co-extrusion side layer extruder with a side layer extruder temperature of 250±5℃. The polymer reinforcing material (6) was fed into a three-layer co-extrusion core layer extruder with a core layer temperature of 240±5℃. The ratio of each side layer to the core layer material was 1:3. The material was melt-extruded, cooled by a 60℃ chilled roller, and then preheated at 120℃, stretched longitudinally by 5 times at 135℃, and shaped at 150℃ in the longitudinal stretching system before being sent to the transverse stretching system. After preheating at 150℃, stretching transversely by 7 times at 165℃, and shaped at 175℃, a 5μmm thick composite current collector base film was obtained.
[0052] Example 11
[0053] The dried polymer polar material (2) was fed into a three-layer co-extrusion side layer extruder with a side layer extruder temperature of 240±5℃. The polymer reinforcing material (5) was fed into a three-layer co-extrusion core layer extruder with a core layer temperature of 240±5℃. The ratio of each side layer to the core layer material was 1:3. The material was melt-extruded, cooled by a roller at 85℃, and then preheated at 125℃, stretched longitudinally by 7 times at 145℃, and shaped at 150℃ in the longitudinal stretching system before being sent to the transverse stretching system. After preheating at 150℃, stretching transversely by 5 times at 175℃, and shaped at 175℃, a composite current collector base film with a thickness of 6μmm was obtained.
[0054] Example 12
[0055] The dried polymer polar material (3) is fed into a three-layer co-extrusion side layer extruder with a side layer extruder temperature of 245±5℃. The polymer reinforcing material (5) is fed into a three-layer co-extrusion core layer extruder with a core layer temperature of 240±5℃. The ratio of each side layer to the core layer material is 1:4. The material is melt-extruded, cooled by roller cooling at 80℃, and then preheated at 130℃, stretched longitudinally by 5 times at 145℃, and shaped at 150℃ in the longitudinal stretching system before being sent to the transverse stretching system. After preheating at 155℃, stretching transversely by 7 times at 170℃, and shaped at 175℃, a 5μmm thick composite current collector base film is obtained.
[0056] Example 13
[0057] The dried polymer polar material (3) is fed into a three-layer co-extrusion side layer extruder with a side layer extruder temperature of 245±5℃. The polymer reinforcing material (6) is fed into a three-layer co-extrusion core layer extruder with a core layer temperature of 240±5℃. The ratio of each side layer to the core layer material is 1:3. The material is melt-extruded, cooled by rollers at 85℃, and then preheated at 125℃, stretched longitudinally by 6 times at 140℃, and shaped at 150℃ in the longitudinal stretching system. After being sent to the transverse stretching system, it is preheated at 150℃, stretched transversely by 7 times at 175℃, and shaped at 175℃ to obtain a composite current collector base film with a thickness of 4μmm.
[0058] Example 14
[0059] The dried polymer polar material (3) is fed into a three-layer co-extrusion side layer extruder with a side layer extruder temperature of 245±5℃. The polymer reinforcing material (7) is fed into a three-layer co-extrusion core layer extruder with a core layer temperature of 160±5℃. The ratio of each side layer to the core layer material is 1:4. The material is melt-extruded, cooled by a 60℃ chilled roller, and then preheated at 90℃, stretched longitudinally by 5 times at 120℃, and shaped at 140℃ in the longitudinal stretching system before being sent to the transverse stretching system. After preheating at 140℃, stretching transversely by 7 times at 145℃, and shaped at 145℃, a composite current collector base film with a thickness of 6μmm is obtained.
[0060] Example 15
[0061] The dried polymer polar material (4) is fed into a three-layer co-extrusion side layer extruder with a side layer extruder temperature of 160±5℃. The polymer reinforcing material (7) is fed into a three-layer co-extrusion core layer extruder with a core layer temperature of 160±5℃. The ratio of each side layer to the core layer material is 1:3. The material is melt-extruded, cooled by a 50℃ chilled roller, and then preheated at 90℃, stretched longitudinally by 5 times at 120℃, and shaped at 125℃ in a longitudinal stretching system before being sent to a transverse stretching system. After preheating at 135℃, stretching transversely by 7 times at 140℃, and shaped at 145℃, a composite current collector base film with a thickness of 4μmm is obtained.
[0062] The properties of the composite current collector base membranes prepared in Examples 8-15 are shown in Table 1.
[0063] Table 1:
[0064]
[0065]
[0066] Note: (1) Tensile strength test shall be conducted in accordance with GB / T 13542.2-2021 Electrical Insulation Films Part 2, Test Methods. MD indicates longitudinal direction, and TD indicates transverse direction.
[0067] (2) Heat shrinkage rate: The longitudinal and transverse heat shrinkage rates were tested after treatment at 120℃ for 10 minutes. MD represents the longitudinal direction and TD represents the transverse direction.
[0068] (3) Electrolyte resistance: The copper-coated film was placed in the electrolyte, vacuumed, and immersed at 60°C. The color change of the electrolyte was observed. The darker the color, the greater the influence of the film on the electrolyte; that is, the darker the color, the worse the effect. The "good," "better," and "poor" in Table 1 are relative comparisons between examples. From the data in Table 1, it can be seen that although we can choose many materials and freely combine them, not all combinations can achieve the required temperature resistance, strength, electrolyte resistance, and copper coating ability (adhesive tape was used, followed by peeling to observe the separation). The "good," "better," and "poor" in Table 1 are relative comparisons between examples.
[0069] In Examples 12-14, the addition of PMMA to the system increased the brittleness of the material. PMMA itself has low strength, and the resulting low elongation at break further reduced the overall strength, hindering subsequent copper plating processes. In Example 15, the presence of materials with poor temperature resistance, such as PVA and PE, resulted in poor overall temperature resistance, making subsequent copper plating processes at 150°C or higher temperatures impossible. In contrast, Examples 8-11 used materials with higher temperature resistance and strength, which improved the overall temperature resistance and strength of the material. Furthermore, the addition of compatibilizers and reinforcing agents significantly improved the temperature resistance, strength, and electrolyte resistance of the final film.
Claims
1. A base membrane for composite current collectors, characterized in that, It includes two layers of polymer polar material and a polymer reinforcing material layer located between the two layers of polymer polar material; The polymer polar material layer includes polyolefin, polar polymer, amphoteric material and antioxidant; The polymer-reinforced material layer includes a polyolefin, a reinforcing material, and an antioxidant; The reinforcing material is one or more of silicon carbide whiskers, aliphatic carboxylic acid metal compounds, and organophosphates; The polar polymer material is one or more of the following: polyethylene terephthalate, polybutylene terephthalate, polydiphenyl ether sulfone, polyvinylidene chloride, polycaprolactam, polydecylformamide, polyhexamethylene sebacate, and polynonylurea. The amphoteric material is one or more of the following: maleic anhydride-grafted PP, GMA-grafted PP, maleic anhydride-grafted PE, GMA-grafted PE, maleic anhydride-grafted POE, GMA-grafted POE, maleic anhydride-grafted EVA, GMA-grafted EVA, maleic anhydride-grafted EPDM, GMA-grafted EPDM, maleic anhydride-grafted SEBS, GMA-grafted SEBS, methyl methacrylate-glycidyl methacrylate-ethyl acrylate terpolymer, maleic anhydride-grafted acrylonitrile-butadiene-styrene terpolymer, and styrene-maleic anhydride random copolymer.
2. The composite current collector base membrane according to claim 1, characterized in that, The polyolefin is one or more of the following: polypropylene, ethylene-acrylic acid copolymer, ethylene-acrylate copolymer, poly-1-butene, poly-4-methyl-1-pentene, and cyclic olefin polymers.
3. The composite current collector base membrane according to claim 1, characterized in that, The thickness of the base film for the composite current collector is 4~6μm, and the thickness of the polymer reinforcing material layer is 50%~90% of the thickness of the base film for the composite current collector.
4. The composite current collector base membrane according to claim 1, characterized in that, The polymer polar material layer includes: 50-95 parts by weight of polyolefin, 5-40 parts by weight of polar polymer material, 0.1-10 parts by weight of amphoteric material and 0.1-0.5 parts by weight of antioxidant.
5. The composite current collector base membrane according to claim 1, characterized in that, The polymer-reinforced material layer comprises 89.5 to 99.8 parts by weight of polyolefin, 0.1 to 10 parts by weight of reinforcing material, and 0.1 to 0.5 parts by weight of antioxidant.
6. A method for preparing a composite current collector base film according to any one of claims 1-5, characterized in that, Includes the following steps: S1. Preparation of polymer polar materials: First, polyolefin, polar polymer material, amphoteric material and antioxidant are mixed evenly, then granulated by twin-screw extruder, and finally granulated by water cooling, air cooling and pelletizing to obtain polymer polar materials; S2. Preparation of polymer-reinforced materials: First, the polyolefin, reinforcing material and antioxidant are mixed evenly, then granulated by a twin-screw extruder, and finally cooled by water, cooled by air and granulated to obtain the polymer-reinforced material; S3. Preparation of composite current collector base film: First, dry the polymer polar material and the polymer reinforcing material; then, feed the dried polymer polar material slices into a three-layer co-extrusion edge layer extruder and the polymer reinforcing material slices into a three-layer co-extrusion core layer extruder. After melt extrusion, the materials are cooled by a chilling roller and then subjected to longitudinal stretching, transverse stretching and shaping in sequence to obtain the composite current collector base film.
7. The method for preparing a composite current collector base film according to claim 6, characterized in that, In steps S1 and S2, the extrusion temperature of the twin-screw extruder is 150℃~300℃; in step S3, the extruder temperature is 150~300℃.
Citation Information
Patent Citations
Composite polymer film, manufacturing method thereof, metalized composite polymer film and application
CN115447248A
Multilayer composite polypropylene material, and preparation method therefor and use thereof
WO2024104393A1